ERGONOMIC APPROACH IN MAINTAINING THE BALANCE AMONG TOURISM ECONOMICAL POTENCIAL IN BALI (with special reference in Singapadu Tengah Village, Sub-district Sukawati, Gianyar regency-Bali) - Parwata, I Wayan; Oesman, Titin Isna (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2011)
At Singapadu Tengah village, sub-district of Sukawati, Gianyar regency is outskirt village with the distance around 10 km from Denpasar city. Since the year 1989, this village has started improving through blossom out of Singapadu Induk village. Site function changes Singapadu Tengah village from agricultural land becomes industrial function and settlement that significantly increases every year. The year of 1990 up to 1995 site function changes around 658 m2 per year, the year 1995 until the year of 2000 reaches 1,09 Ha per year, while in the year of 2000 up to 2005 reaches 1,67 Ha per year. This site function change has caused among others 1) high migration current come to Bali in this time has spread to village area in Bali; 2) arrangement of development distribution by the government has not been yet assertive; 3) the low value of the agricultural product selling, and the agricultural land tax is up; 4) as a result of irrigation system that chage into the connected irigation channel; and 5) consumerism. Through total approach in the ergonomic scope, it is expected to improve the condition of agriculture that is more and more depressed effect as the result from influences of site function change. SHIP (Systematical, Holistic, Interdisciplinary and Participatory) approach as part of total approach is one of the way to maintain function of agricultural land as a sector capable to support public economics in Bali.